Pengaruh Good Corporate Governance Terhadap Keandalan Laporan Keuangan Di Perusahaan Campina Ice Cream (Study Kasus Tahun 2023) - Dharma, Angeline Suhandra; Limanatan, Andrea Ivanka (Innovative: Journal Of Social Science Research, 2024)
This research aims to analyze the effect of implementing Good Corporate Governance (GCG) on the reliability of financial reports at PT Campina Ice Cream Industry Tbk in 2023. The research method used is quantitative, with data collection techniques through documentation of the company's annual financial reports. GCG implementation is measured using an index that includes managerial ownership and audit committee size, while the reliability of financial reports is assessed through audit results and the suitability and transparency of information. The research results show that the GCG index reached 100%, reflecting optimal implementation of the principles of transparency, accountability, independence, responsibility and fairness. The reliability of financial reports also reaches maximum value, which is demonstrated through the disclosure of information that is accurate and in accordance with accounting standards. This research proves the positive influence of GCG implementation on the reliability of financial reports, which supports stakeholder decision making. This research provides a theoretical contribution by adding to the literature regarding the relationship between GCG and the quality of financial reports in the food and beverage sector, as well as practical recommendations for companies in maintaining consistent GCG implementation.